Assessing the Combined Impacts of Future Climate and Land Use Changes on Soil Loss and Sediment Retention in the Lam Phra Phloeng Watershed, Thailand - Seeboonruang, Uma; Mandadi, Ranadheer; Thammaboribal, Prapas; Gonzales, Arlene L.; Kanchan, Arun; Ganni, Satya Venkata Sai Aditya Bharadwaz (My University, 2025)
Soil erosion is a significant challenge to the environment, ecology, and economy, and areas that undergo fast land use change and climate change are the most affected. This research evaluates the effects that climate change and Land-Use/Land-Cover (LULC) change have, separately and together, on soil loss and sediment retention in the Lam Phra Phloeng (LPP) watershed, Thailand. The InVEST Sediment Delivery Ratio (SDR) model was applied under the Shared from Socioeconomic Pathways (SSP2-4.5 and SSP5-8.5), using projected LULC for 2050 and 2100. The Cellular Automata–Markov (CA–Markov) model has been utilized to generate future land use/land cover (LULC) scenarios demonstrating how land changes over spatial and temporal scale. Results show a marked decline in sediment retention and a rise in soil loss, especially under high-emission scenarios and cropland expansion. By 2100, cropland soil loss increased by 57.35%, while forest cover—a key determinant of sediment retention—declined from 45.41% in 2020 to 22.19%. When climate and land-use changes are considered together, they have a much greater effect on sediment loss, especially in cropland and built-up areas. These results highlight the vital role that forest conservation and adaptive land management, e.g., afforestation and sustainable agriculture, play in ensuring the continued availability of clean water in watersheds and in erosion control. The research provides policy-makers with real-life scenarios to draw on when sketching integrated watershed management plans aimed at reducing the negative effects of land use and climate change on soil stability and water resources in the LPP watershed.
Keywords: climate variability; ecosystem services; erosion risk; hydrological modeling; InVEST SDR model; land-use dynamics; Southeast Asia; watershed management